Metabolic profiling reveals local and systemic responses of kiwifruit to Pseudomonas syringae pv. actinidiae. (16th December 2020) - Li, Yawei; Wang, Xiaojie; Zeng, Yunliu; Liu, Pu
Abstract: Pseudomonas syringae pv. actinidiae ( Psa ), a bacterial pathogen, causes bacterial canker disease in kiwifruit. To elucidate the local and systemic influences of Psa infection on kiwifruit, comprehensive analyses were conducted by combining metabolomic and physiological approach under Psa ‐infected treatment and mock‐inoculated control in leaves, stems, and bleeding saps. Our results show that Psa infection stimulated kiwifruit metabolic reprogramming. Levels of many sugars, fumarate, and malic acid were decreased in Psa ‐infected leaves and stems, accompanied by the increased level of amino acids (AAs), which implies the anaplerotic reaction to replenish the TCA cycle generating energy and intermediates for defense‐related metabolic pathways, such as phenylpropanoid metabolism. The inconsistent results were observed in bleeding saps, which may be attributed to the induced phloem transport of carbon (C) out of leaves and such a transport benefits bacterium movement. Arg, Gln, and pyroglutamic acid systematically were accumulated in long‐distance leaves, which probably confers to systemic acquired resistance (SAR) and Psa inoculation accelerated the nitrogen (N) cycling in kiwifruit. Moreover, Psa infection specifically affected the content of phenolic compounds and lignin. Phenolic compounds were negatively and lignin was positively related to kiwifruit Psa resistance, respectively. Our results first reveal that Psa enhances infection by manipulating C/N metabolism and sweet immunity, and that host lignin synthesis is a major physical barrier for restricting bacterial infection. This study provides an insight into the complex remodeling of plant metabolic response to Psa stress.